2017
DOI: 10.3390/ijms18091847
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotide Ameliorates Lipopolysaccharide-Induced Lung Injury by Inhibiting Apoptotic Cell Death in Rats

Abstract: Lung injury is characterized by diffuse lung inflammation, alveolar-capillary destruction, and alveolar flooding, resulting in respiratory failure. Polydexyribonucleotide (PDRN) has an anti-inflammatory effect, decreasing inflammatory cytokines, and suppressing apoptosis. Thus, we investigated its efficacy in the treatment of lung injury, which was induced in rats using lipopolysaccharide (LPS). Rats were randomly divided into three groups according to sacrifice time, and each group split into control, lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In general, ROS generation and complement activation occur early during reperfusion 24 . It has been stated that lung injury was characterized in histological sections with diffuse lung inflammation, alveolar-capillary destruction, and alveolar flooding, resulting in respiratory failure 25,26 . In our histological study, we found lung injury such as intra-alveolar hemorrhage, inflammatory cell infiltration in the contol-saline+IR group.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ROS generation and complement activation occur early during reperfusion 24 . It has been stated that lung injury was characterized in histological sections with diffuse lung inflammation, alveolar-capillary destruction, and alveolar flooding, resulting in respiratory failure 25,26 . In our histological study, we found lung injury such as intra-alveolar hemorrhage, inflammatory cell infiltration in the contol-saline+IR group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has suggested that the main pathogenic mechanisms of ALI include oxidative stress, cytokine release, inflammation and apoptosis [36]. During ALI, large amounts of ROS are generated, which cause cell membrane lipid peroxidation and the destruction of lung parenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first group of articles analyzes different possible pathways of the immune and inflammatory response, before proposing possible diagnostic and treatment interventions [2][3][4][5]. Douglas et al [2] analyzed the evidence from the literature on the enhancement of upper respiratory innate immunity due to bitter taste receptors and the possible roles of individual taste differences in the clinical management of patients with upper respiratory infections.…”
Section: Reviewmentioning
confidence: 99%